Antiphospholipid Syndrome, Review of 24 Iraqi patients - Yassin, Ahmed Kh.; Jawad, Ali M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Antiphospholipid syndrome (APS) is a disorder in which vascular thrombosis and / or recurrent pregnancy losses occur in a patient who has laboratory evidence of antibodies against phospholipids or phospholipids binding protein cofactor. Usually the patient presents at an age between 35- 45 years, with equal male to female ratio. Mostly they present with thrombosis or pregnancy complication. A quarter of the patients have thrombocytopenia and about one fifth have hemolytic anemia. The diagnosis rests on the criteria set as the Revised classification criteria for the Antiphospholipid syndrome Patients and Methods; During the period from 1st Jan. 2002 until the 1st Jan. 2006,24 patients who met the criteria of APS (according to Revised classification criteria for the Antiphospholipid syndrome) were included in the study. The diagnosis of deep venous thrombosis (DVT) was done by using Doppler study of the selected organ, while brain CT and magnetic resonance imaging were used to diagnose cerebrovascular thromboses.Serological evidence of APA were either an abnormal KCT and KCT index and/or a positive aCL antibody test on 2 occasions. Results : Three quarter of our patients were females, more than half of them aged 21-30 years ,54.16% of our patients presented with thrombosis the commonest site of which was DVT of lower extremities. Abortion alone was the presenting problem in two patients and two patients presented with thrombosis following abortion Another two patients presented with bleeding problems. Gathering the history; follow up abortion occurred in ten of the thirteen premenapausal married ladies, of whom five had more than three abortions.evaluation revealed anemia in 8 patients (33.33% ) and thrombocytopenia in 5 patients (20.8% ).The KCT and KCT index were suggestive of APS in 14 of the 23 patients tested (60.86%)and the aCL was positive in 15 of the 19 tested patients (78.94 %). Conclusion, We think that our study, although small, highlights some of the clinical and laboratory findings of this syndrome in Iraqi patients, larger studies are needed for better evaluation.